Investigating the closures of sea level budgets in China’s adjacent seas - Yang Li; Jinyun Guo; Yu Sun; Jiangcun Zhou; Heping Sun (Scientific Reports)
Abstract Regional relative sea level changes are most relevant for coastal communities and remain challenging to understand. China’s adjacent seas are among the world’s most vulnerable regions to sea level rise. This paper investigates the sea level budgets in China’s adjacent seas over the past 20 years. We use multiple time-varying gravity field data and steric data to assess the uncertainties of some components in the sea level budget and the contributions of mass loss from ice sheets, glaciers, and terrestrial water storage changes to regional relative sea level changes were estimated using sea level fingerprints. The sea level budget results based on ensemble mean data show that the root mean square errors of the budget residuals in the Bohai Sea, Yellow Sea, East China Sea, South China Sea, and Northwest Pacific are 40±3 mm, 52±4 mm, 36±2 mm, 23±2 mm, and 11±1 mm, respectively. A single dataset fails to close the long-term sea level trends for all regions within a 65% confidence interval. We discussed the impacts of each component on the budget residuals and identified steric data and the ocean dynamics model as the main reasons for the excessive residuals. The de-aliasing product of the GRACE satellite, AOD1B model, is primarily responsible for the strong interannual signals in the residuals of the sea level budget in the Bohai Sea, Yellow Sea, and East China Sea.